Pengaruh ROA dan Nilai Pasar Terhadap Carbon Emission Disclosure: Studi Kasus pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2021-2024 - Nurjamilah, Imas Siti; Hartikayanti, HN. (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Climate change issues and increasing demands for environmental transparency require companies to be more open in disclosing carbon emissions. However, the level of carbon emission disclosure in Indonesia remains relatively low and varies across companies, making it important to investigate the factors that influence such disclosure. This study aims to examine the effect of Return on Assets (ROA) and market value on carbon emission disclosure. Carbon emission disclosure represent a form of corporate transparency in addressing environmental issues, particularly those related to sustainability and social legitimacy. This research employes a quantitative method with a descriptive and associative approach. The population consisted of energy sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The sample was selected using purposive sampling, resulting in 21 companies as the research objects with a total of 84 sample. Data analysis was carried out through classical assumption tests, multiple linear regression, correlation and determination tests, including t-tests and F-tests. The findings indicate that ROA has no significant effect on carbon emission disclosure, while market value exerts significant effect on carbon emission disclosure.”